The association between epstein-barr virus (EBV) past infection with the risk of oral squamous cell carcinoma (OSCC) - Jesinda P Kerishnan,; Mah, Ming-Kit; Nurul Ain Mohd Fawzi,; Anand Ramanathan,; Lim, Ghee-Seong; Azwatee Abdul Aziz,; Usharani Balasingam,; Chen, Yeng (Penerbit Universiti Kebangsaan Malaysia, 2019)
The association of Epstein-Barr virus (EBV) with oral cancer has been widely reported in the past. However, previous studies mainly focused on the current infection of EBV without acknowledging the possibility of past infection in patients which may lead to oral cancer development. The present study aims to investigate the correlation between past EBV infections with Oral Squamous Cell Carcinoma (OSCC). Both Immunoglobulin M (IgM) and Immunoglobulin G (IgG) antibodies against EBV were screened to detect the presence of EBV in sera of OSCC patients using Enzyme-Linked Immunosorbent Assay (ELISA). The use of IgM antibody against EBV confirms current infection in patients, whereas IgG antibody would predict past infection throughout patients’ lifetime. Through the present study, we would be able to confirm whether patients with past EBV infection have a significant risk in developing oral cancer. ELISA tests were carried out to detect the presence of EBV IgG and IgM in 206 OSCC and control serum samples. Statistical analysis was performed using SPSS 12.0.1. Our results had shown that 96.6% (n = 199) of OSCC samples and 97.2% (n = 130) control were positive with EBV VCA IgG, however, none of the OSCC and control samples was positive for EBV VCA IgM. The presence of EBV VCA IgG in both OSCC and control suggest that past EBV infection does not play a significant role as a risk indicator for OSCC. Therefore, the association between EBV and OSCC was not well demonstrated in this study.